Design application e-raport with framework Codeigniter (case study of SMP N 1 Singorojo (Information Technology and Telematics, 2015)
ABSTRACT The problem for processing the value of rapport is one of the many of subsystem that must be face in the school. This thing cause the activity that related with academic system become smooth less, like it takes a long process to search for a student scores and the teacher data will take for more than one day to process, like a task scores, daily tests, midterm exam, also for final exam and calculation process assessment. E-Rapport Application Design is one of the solutions to face the problem above, by using the Information Technology of this era, work efficiency in the assessment process of student scores in SMP 1 Singorojo Kendal will be fulfill. This Application was made by using Codeigneter framework. Keywoard: E-Raport, design, Framework Codeigniter.